2016
DOI: 10.1097/md.0000000000004453
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of 24-hour intraocular pressure rhythm in healthy Shanghai population

Abstract: The aim of the present study was to investigate and compare the 24-hour intraocular pressure (IOP) rhythms in winter and summer in the healthy population of Shanghai, China.This is a cross-sectional study in which 24-hour IOP measurements were taken for all eligible healthy volunteers in winter and summer, respectively, and the temperature, hours of sunlight (sunlight time), and circulatory parameters, including heart rate, systolic blood pressure, and diastolic blood pressure, were also recorded. The 24-hour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Our results are compatible with previous studies of a seasonal fluctuation in IOP 21,22 wherein IOP was higher during the winter than the summer by 0.5 mmHg for non-glaucoma patients without DED and by 1.0 mmHg for glaucoma patients without DED. Glaucoma medications might not contribute to this fluctuation since they tend to instead reduce the magnitude of diurnal fluctuations 23,24 .…”
Section: Discussionsupporting
confidence: 93%
“…Our results are compatible with previous studies of a seasonal fluctuation in IOP 21,22 wherein IOP was higher during the winter than the summer by 0.5 mmHg for non-glaucoma patients without DED and by 1.0 mmHg for glaucoma patients without DED. Glaucoma medications might not contribute to this fluctuation since they tend to instead reduce the magnitude of diurnal fluctuations 23,24 .…”
Section: Discussionsupporting
confidence: 93%
“…Findings from this study provide a new perspective on prior reports of seasonal variations in IOP observed in both healthy (Cheng et al, 2016;Qureshi et al, 1996) and ocular hypertensive humans (Gardiner et al, 2013;Qureshi et al, 1999). These studies show that IOP tends to be higher during winter months, which has been attributed to reduced sunlight exposure.…”
Section: Discussionsupporting
confidence: 62%
“…All subjects underwent 24-h IOP monitoring at Beizhan Hospital using published methods [ 4 , 8 ]. In brief, participants were asked to maintain normal biological activities and rhythms, and were housed in special area of the hospital a day in advance of the 24-h recording.…”
Section: Methodsmentioning
confidence: 99%
“…There were previous researches demonstrating that long-term IOP fluctuation is significantly related to the risk of glaucoma progression [2,3]. Twentyfour-hour IOP monitoring [4][5][6][7][8] and its association with glaucomatous optic neuropathy needs further investigation.…”
Section: Introductionmentioning
confidence: 99%